Adriatic sailors and stone knappers : PalagruZa in the 3rd millennium BC - Kaiser, Timothy
Small islands offer archaeologists interesting and manageable subjects for survey and excavation. The recent work on Adriatic islands reported here examines occupation during the 3rd millennium BC, showing how sailors exploited islands for trade, control and raw materials.